Workstation Hazards and Biomechanical Risk Factors in Informal Welding Sectors of Northern Nigeria - Suleiman Mohammed; Mannir Kassim; Hamza Sabo Muhammad; Bishir Sabo; Usman Gidado (African Journal of Medicine, Surgery and Public Health Research, 2026)
Within the unorganized industrial landscapes of sub-Saharan Africa, ground-level fabrication remains a common operational practice that exposes artisans to substantial ergonomic risks. Although musculoskeletal morbidity is widespread in informal welding work, the biomechanical mechanisms and socio-behavioural coping strategies used by artisans remain under-researched. This study evaluates the ergonomic risk profile and compensatory behaviours among artisanal welders in Maiduguri, Borno State, Nigeria. A systematic ergonomic audit was conducted among 306 artisanal welders to quantify environmental deficits, postural deviations, particularly trunk and cervical flexion, and manual material handling frequencies. Participants’ coping mechanisms were categorized into physical, pharmacological, and socio-economic domains. Data were analyzed using descriptive statistics and Pearson’s chi-square tests at the p < .05 significance level. The findings revealed a profound structural deficit, with 91.2% of fabrication tasks performed without elevated work surfaces. Dominant pathological postures included sustained trunk flexion exceeding 30° (56.2%) and prolonged squatting. To sustain work capacity, 85.3% of respondents almost always relied on pharmacological intervention, while 56.2% engaged in reactive postural shifting. In addition, 72.8% used social capital by delegating high-strain tasks to apprentices. Despite these adaptations, 38.8% of the workforce reported multi-day work absences due to physical incapacity, indicating substantial erosion of productive capacity. The study concludes that informal welding in Maiduguri is characterized by severe ergonomic stressors that exceed individual physiological coping capacity. The findings contribute to occupational ergonomics by showing that prevailing coping strategies are largely palliative and may reinforce cycles of pharmacological dependence, productivity loss, and premature professional attrition. The study recommends ergonomic modernization through low-cost engineering interventions, particularly improved workstation design, to protect the health and sustainability of this vital informal workforce.